Educação ambiental no ensino superior: uma análise em cursos de secretariado executivo - Sanches-Canevesi, Fernanda Cristina; Schmidt, Carla Maria; Hoffmann, Larisse Daniela; Cielo, Ivanete Daga; Yaegashi, Solange Franci Raimundo (Universidade Estadual de Campinas, 2020)
The theme of sustainability is relevant considering the current need of man in relation to the preservation of the environment for the future generations. The Environmental Education (EE) emerged as a way to rethink strategies aimed at sustainability. As the EE should be practiced at all levels of education, including in higher education, this article aimed to understand if / how the EE is inserted in the Pedagogical Projects of the Executive Secretariat courses of Public Higher Education Institutions in Brazil. Also, this study objetives investigate the perception of academics of an institution in relation to the theme. For this, this study did a documentary research and a questionnaire application with the academics from the last undergraduate period of the analyzed Institution. As main results, it was identified that six Institutions have subjects/content focused on EE. Still, it was found that the academics of the investigated university perceive the importance of studying themes related to sustainability and EE.